DARK HERITAGE TOURISM IN THE IBERIAN PENINSULA, BY SARA CERQUEIRA PASCOAL, LAURA TALLONE AND MARCO FURTADO (Eds). - Navajas-Corral, Óscar (POLISSEMA – Revista de Letras do ISCAP, 2023)
Reseña de libro: Dark Heritage Tourism in the Iberian Peninsula